2013
DOI: 10.1155/2013/837010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Rotor Slot Number on the Behaviour of the Induction Motor

Abstract: The impact of the rotor slot number selection on the induction motors is investigated. Firstly, analytical equations will reveal the spatial harmonic index of the air gap magnetic flux density, connected to the geometrical features and the saturation of the induction motor. Then, six motors with different rotor slot numbers are simulated and studied with FEM. The stator is identical in all motors. The motors are examined under time-harmonic analysis at starting and at 1440 rpm. Their electromagnetic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Similarly, in the case when the number of rotor bars is a divisor of 2p(mz1), upper RSHs exists in stator current spectrum at frequencies given by (10) and associated upper pulsating torque components at frequencies given by (12).…”
Section: Optimal Number Of Rotor Bar Selectionmentioning
confidence: 98%
“…Similarly, in the case when the number of rotor bars is a divisor of 2p(mz1), upper RSHs exists in stator current spectrum at frequencies given by (10) and associated upper pulsating torque components at frequencies given by (12).…”
Section: Optimal Number Of Rotor Bar Selectionmentioning
confidence: 98%
“…The reaction of the rotor cage on the flux density waves from stator is given by the following MMF waves [11,16]:…”
Section: A Analytical Calculation A1 Stator and Rotor Mmfmentioning
confidence: 99%
“…According to [16], the air-gap relative permeance takes the following form in order to take into account the iron core saturation, considering the fundamental harmonic:…”
Section: Saturation Harmonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [29], it has been shown that the radial component of the air-gap magnetic flux density can be calculated by…”
Section: Calculation Of the Magnetic Flux Density Harmonicsmentioning
confidence: 99%